1981
DOI: 10.1128/jcm.13.5.899-907.1981
|View full text |Cite
|
Sign up to set email alerts
|

Gas-chromatographic analysis of mycolic acid cleavage products in mycobacteria

Abstract: Mycolic acids were detected in both reference strains and clinical isolates of mycobacteria by using gas chromatography of fatty acid methyl esters prepared by acid methanolysis. The methyl esters were extracted with hexane, concentrated, and analyzed with a gas chromatograph by using two different injector temperatures. When the samples were analyzed at high injector temperatures of 300 to 350°C, characteristic thermal cleavage products from mycolic acids, C220, C240, or C260 fatty acid methyl esters, were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
4

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 20 publications
2
19
0
4
Order By: Relevance
“…Because of the abundance of mycolic acids in mycobacterial species, several studies have addressed the separation of compounds of both types, i.e., those with chains of >20 carbons (mycolic acid cleavage products) and those with chains of <20 carbons (constitutive fatty acids) (58,87,150). Quantitative analysis of fatty acids belonging to these two groups results in accurate identification to the species level (58,69,82,150,151). Among isolates encountered over a 2-year period, Jantzen et al 69determined that M. tuberculosis could be identified without exception, largely on the basis of C26:0 at concentrations of 1 to 13%.…”
Section: Identification To Genus or Speciesmentioning
confidence: 99%
“…Because of the abundance of mycolic acids in mycobacterial species, several studies have addressed the separation of compounds of both types, i.e., those with chains of >20 carbons (mycolic acid cleavage products) and those with chains of <20 carbons (constitutive fatty acids) (58,87,150). Quantitative analysis of fatty acids belonging to these two groups results in accurate identification to the species level (58,69,82,150,151). Among isolates encountered over a 2-year period, Jantzen et al 69determined that M. tuberculosis could be identified without exception, largely on the basis of C26:0 at concentrations of 1 to 13%.…”
Section: Identification To Genus or Speciesmentioning
confidence: 99%
“…Mycolic acid cleavage products. The two commonly occumng constituents tetracosanoate (24:O) and hexacosanoate (26:O) of Table 1 are pyrolytic cleavage products of mycolic acids (6,7,14). In agreement with several reports (9,13,14,17,28) we found the amounts of these two products to be reasonably reproducible (Table 1 ), although Lambert et al reported otherwise (10).…”
Section: Main Dj Ffermtiating Jeaturesmentioning
confidence: 99%
“…A variety of GLC methods have been developed in an attempt to differentiate mycobacteria by identifying their complex mycolic acids. Guerrant et al (8) used GLC to examine mycolic acid methyl ester cleavage products of several mycobacterial species and showed the potential of this system for differentiating mycobacteria; however, because of the limited number of species tested and the complexity of the methyl mycolates, the methodology had limited practical application. In recent years, GLC profiles of mycobacterial fatty acid methyl esters has appeared more useful for speciating mycobacteria (1,3,12,21,22).…”
mentioning
confidence: 99%